Molecular beam epitaxial growth of dilute nitride GaNAs and GaInNAs nanowires. (26th March 2019) - Yukimune, M; Fujiwara, R; Mita, T; Tsuda, N; Natsui, J; Shimizu, Y; Jansson, M; Balagula, R; Chen, W M; Buyanova, I A; Ishikawa, F
Abstract: We report the growth of dilute nitride GaNAs and GaInNAs core-multishell nanowires (NWs) using molecular beam epitaxy assisted by a plasma source. Using the self-catalyst vapor–liquid–solid growth mode, these NWs were grown on Si(111) and silicon on insulator substrates. The GaNAs and GaInNAs shells contain nitrogen up to 3%. Axial cross-sectional scanning transmission electron microscopy measurements and energy-dispersive x-ray spectrometry confirm the formation of the core-multishell NW structure. We obtained high-quality GaNAs NWs with nitrogen compositions up to 2%. On the other hand, GaNAs containing 3% nitrogen, and GaInNAs NWs, show distorted structures; moreover, the optical emissions seem to be related to defects. Further optimisations of the growth conditions will improve these properties, promising future applications in nanoscale optoelectronics.